Kewirausahaan Sosial dalam Pemberdayaan Ekonomi Umat - Mandala Faldini (MAWA IZH JURNAL DAKWAH DAN PENGEMBANGAN SOSIAL KEMANUSIAAN, 2017)
Social entrepreneur is a branch of entrepreneur. Solutions of social problems who implementated is a social entrepreneur. A social entrepreneur be required a person who can read a social problem, design a social solution and mobilize the idea in order to implemented. Entrepreneur with social motivation, makes a lot of impact. Social impact of entrepreneur is fullfilment of needs, serve alternative unique product with low cost and provide solutions of goverment problems. Indonesia as a country with muslims as mayority, social entrepreneur is a needs for people economy. Social entrepreneur can be solution of economic gap or disparities in Indonesia.